Widespread White Matter Alterations in Patients with End-Stage Renal Disease: A Voxelwise Diffusion Tensor Imaging Study - Chou, M.-C.; Hsieh, T.-J.; Lin, Y.-L.; Hsieh, Y.-T.; Li, W.-Z.; Chang, J.-M.; Ko, C.-H.; Kao, E.-F.; Jaw, T.-S.; Liu, G.-C. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: ESRD results in excessive accumulation of urea and toxic metabolites. Hemodialysis is usually performed to maintain health in patients with ESRD; however, it may cause silent white matter alterations in the earlier stages. Hence, this study aimed to perform voxelwise diffusion tensor analysis for global detection of subtle white matter alterations in patients with ESRD. MATERIALS AND METHODS: Twenty-eight patients with ESRD and 25 age-matched control subjects were enrolled in this study. Each subject underwent CASI assessment and DTI. After spatial normalization of DTI images, voxelwise statistical analyses were performed to compare DTI parameters between the 2 groups. RESULTS: In patients with ESRD, AD, RD, and MD values were significantly increased, whereas the FA value was significantly decreased, mostly in the corpus callosum, bilateral sagittal stratum, and pons. Multiple regression analysis further revealed that both RD and MD were positively correlated with the duration of hemodialysis in the pons; however, no significant correlation was observed with FA. Negative correlations of RD and MD and a positive correlation of FA with the CASI score were observed in the corona radiata. CONCLUSIONS: We concluded that voxelwise DTI analysis is helpful in the detection of white matter alterations caused by hemodialysis. ADaxial diffusivityCASICognitive Abilities Screening InstrumentESRDend-stage renal diseaseFAfractional anisotropyMDmean diffusivityRDradial diffusivity